Difference in physical properties of MAX-phase compounds Cr2GaC and Cr2GaN induced by an anomalous structure change in Cr2GaN. (February 2019) - Tong, Haiyun; Lin, Shuai; Huang, Yanan; Tong, Peng; Song, Wenhai; Sun, Yuping
Abstract: MAX-phase compounds with layered structure have been investigated extensively due to their excellent metallic and ceramic properties. Among them, Cr2 GaC and Cr2 GaN possess the same crystal structure and similar electronic structure, whereas Cr2 GaN undergoes a spin-density-wave transition around 170 K but Cr2 GaC is Pauli paramagnetism without any magnetic transition. To understand what make these happen, we studied the crystal structure between 300 and 35 K for both Cr2 GaC and Cr2 GaN. As the temperature decreases, the lattice constants (both a and c ) decline monotonically in Cr2 GaC, while an abnormal negative thermal expansion of c axis was observed below 170 K in Cr2 GaN. The increase of c/a induced by abnormal increase of c leads to the enhancement of localization of Cr2 N plane and causes more Cr-3 d electrons confinement in Cr2 N plane of Cr2 GaN. This further facilitates the reconstruction of density of states near the Fermi surface and even forms the Fermi surface nesting, resulting in the spin-density-wave transition as well as the abrupt changes of resistivity, specific heat, and density of carriers around 170 K in Cr2 GaN. Graphical abstract: We reported microtopography as well as temperature dependent resistivity, specific heat, and density of carriers in isostructural Cr2 GaC and Cr2 GaN, and there exists considerable differences. To make it clear, we investigated the changes of structure with temperature between 300 and 35 K in both Cr2 GaC and Cr2 GaN. The anomalous increase of lattice constant c and c/a ratio were observed around 170 K in Cr2 GaN, which is the inducement of spin-density-wave and the origin of anomalous changes in resistivity, specific heat, and density of carriers in Cr2 GaN. Therefore, the biggest difference between Cr2 GaC and Cr2 GaN is just an anomalous structure change of Cr2 GaN. Highlights: We firstly reported the negative thermal expansion of c axis below 170 K in Cr2 GaN, leading to an anomalous increase of c / a. Differences were observed in microtopography, resistivity, specific heat, and density of carriers between Cr2 GaC and Cr2 GaN. Anomalous structure changes at 170 K cause the reconstruction of density of states near Fermi surface in metallic Cr2 GaN.